Levels, trends and socio-economic correlates of caesarean section deliveries: District level analysis in Karnataka, India - Javeed A. Golandaj; Jyoti S. Hallad (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - Caesarean section (CS) is being used as a life-saving surgical tool when complications arise in the process of childbirth. CS rates have dramatically increased across the world, especially in recent decades. In this background, the purpose of this paper is to explore the CS rates and its determinants in Karnataka, India. Design/methodology/approach - The study uses multiple rounds of the District Level Household Survey (DLHS) data to show the trends, differentials and determinants in CS deliveries. Both bivariate and multivariate analyses have been carried out, and the χ2 test and logistic regression models were applied. Findings - Result shows a sharp increase in CS rates across Karnataka; further, this is high and reaches an alarming level in southern parts of the state. Along with a huge rural-urban difference, significant biological and socio-economic differences were observed. Further, a very dramatic increase in the CS rate was observed in private health facilities, whereas it was stagnant or even decreased in public health facilities during recent years. Mothers age at birth, birth weight, birth order, multiple births, birth institution and place of residence were significantly associated with CS delivery. Unlike these biological factors, the social-economic factors like maternal education, caste, religion and below poverty line household were not found to be significant in determining CS deliveries. Originality/value - A strong policy to address the dramatic increase in CS deliveries is the need of the hour. Further, there should be a proper mechanism at national, state and sub-state level to provide appropriate checks and monitoring for CS deliveries which are unnecessary.